Application of Acupressure Therapy to Reduce Blood Pressure in Hypertension Patients - Hanny Irmaya; Hendrawati Hendrawati; Juwita Winnar (Indonesian Journal of Global Health Research, 2026)
Hypertension is a condition of increased systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg, which has the potential to cause various cardiovascular complications if not optimally managed. Hypertension can be managed through pharmacological and non-pharmacological therapies. One non-pharmacological method that can be used is acupressure therapy, a stimulation technique in the form of pressure on certain points on the body that aims to increase relaxation and improve blood circulation. This study aims to determine the effectiveness of applying acupressure therapy in reducing blood pressure in hypertension patients. The research method used is qualitative research with a descriptive case study approach. The study subjects consisted of four respondents with hypertension. Data collection was carried out through interviews, observations, physical examinations, and blood pressure measurements before and after the intervention according to standard operating procedures. The acupressure therapy intervention was carried out for two weeks with a total of six meetings. Data was analyzed using thematic analysis. The results showed that before the intervention, the respondents' blood pressure was in the range of 150–170 mmHg for systolic and 90–110 mmHg for diastolic. After acupressure therapy, all respondents experienced a decrease in blood pressure, with systolic blood pressure ranging from 8–14 mmHg and diastolic blood pressure between 10–14 mmHg. These results indicate that acupressure therapy is effective in lowering blood pressure in patients with hypertension. Acupressure therapy can be considered a complementary non-pharmacological intervention in the management of hypertension.